(untitled) (Khairulummah, 2023)
Breaking a prolonged silence in the anarchic international arena, China initiated a Big bang infrastructure development program in 2013, containing about 2600 projects with net worth of 3.7 trillion dollars in 140 different countries. This mega project may bring a great change to the developing nations and that’s why it is regarded as a great opportunity for the developing world but at the same time it is regarded as a threat to the developed big democracies of the world. This colossal project of China result as a tool for China to be global super power in this multipolar world order which is totally unacceptable to the United States of America. So in this regard G7 countries launched another infrastructure program for the developing world as a counter balance to BRI. Pakistan is a major party to this gigantic project of China through CPEC; the so called flagship project, which worth about 62 billion dollar. This project will be proven as a „‟ game changer‟‟ for both China and Pakistan if get succeeded in true sense. Pakistan always welcome infrastructure development on its land, In this way Pakistan don’t want to indulge itself in Sino-US rivalry or don’t want to be a party of another cold war, so it is willing to participate in B3W also. In this paper, I am going to discuss the details about BRI, its projects and policies and also investment in these projects. This paper will provide details about how and why BRI is regarded as a threat for some countries while at the same time it is a great opportunity for developing nations. I will discuss its advantages and opportunities as well as its defects and how Pakistan’s is a part of this project and also Pakistan’s stance on B3W in this paper. Regarding its defects I mentioned some recommendation after my research findings to achieve its basic objective. It is hoped that the research findings and recommendations will be initialized by the government authorities.